PENGARUH KUALITAS PRODUK DAN IKLAN TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN DI PT. GRAHA KONSTRUKSI SEJATI - MEDAN - M. Tahir (Universitas Islam Islam Sumatera Utara, 2019)
The problem that occured in the company is concerned about the quality of the properties built. Most of the houses built does not meet the prescribed standards , so that it led to the low property purchasing decisions by prospective customers. Another problem that arises is the lack of advertising done. Method of data collection was conducted by questionnaire. The method of analysis used is multiple regression. The population were all consumers of PT. Graha Konstruksi Sejati amounting to 150 people . The samples in this study were chosen using formula of Slovin with error rate of 5 %. The total sample were 109 consumers and the sampling method used was simple random sampling. The results of research as shown in the hypothesis indicate that the quality products and advertisiment simultaneously and partially have significant effect on consumer purchase decisions.